2018
DOI: 10.1080/01431161.2018.1523580
|View full text |Cite
|
Sign up to set email alerts
|

Hot monkey, cold reality: surveying rainforest canopy mammals using drone-mounted thermal infrared sensors

Abstract: Animals of the rainforest canopies are often endangered by deforestation or hunting but are difficult to survey and study because of the inaccessibility of the treetops, combined with the visual camouflage of many species. Drone-based thermal sensors have the potential to overcome these hurdles by rapidly scanning large forested areas from above, detecting and mapping wildlife based on the contrast between their warm body temperatures and the cool tree canopies. We tested this concept by flying a drone-mounted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
94
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 106 publications
(99 citation statements)
references
References 22 publications
4
94
1
Order By: Relevance
“…Conversely to our findings, Kays et al, 2019 [23] found that ground counts were higher than drone counts. However, they compared counts from only two flights, whereas we compared counts from 28 flights.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Conversely to our findings, Kays et al, 2019 [23] found that ground counts were higher than drone counts. However, they compared counts from only two flights, whereas we compared counts from 28 flights.…”
Section: Discussioncontrasting
confidence: 99%
“…In addition to spider monkeys, the Yucatan Peninsula is home to black howler monkeys (Alouatta pigra), but they are very rare in Los Arboles Tulum. Other animals of similar size to spider monkeys (e.g., coatis, small cats) occupy lower vegetation layers and will therefore be more difficult to detect in TIR drone footage [23]. None of these species were observed near the monkeys during our ground observations.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations